Effect of chemotherapy on the outcome of self-expandable metallic stents in gastric cancer patients with malignant outlet obstruction - Kim, C. G.; Park, S. R.; Choi, I. J.; Lee, J. Y.; Cho, S. J.; Park, Y. I.; Nam, B. H.; Kim, Y. W. (Endoscopy, 2012)
Background and study aim: Chemotherapy has been suggested to affect the outcome of pyloric stent placement. This study aimed to investigate the association between the response to chemotherapy and pyloric stent outcome.Patients and methods: Data from 113 patients with inoperable gastric cancer who received chemotherapy after pyloric stent placement at the National Cancer Center hospital were analyzed retrospectively. Chemotherapy response was assessed using the Response Evaluation Criteria in Solid Tumors. A Cox proportional hazards model was used to evaluate the effect of chemotherapy response on the complications of stents.Results: The stent migration rate was 15.9 % (18/113) and the re-stenosis rate was 30.1 % (34/113). The response rates to chemotherapy were higher in the first-line group than in the salvage chemotherapy group (second-line or more) (44.8 % [26/58] vs. 3.6 % [2/55], respectively; P < 0.001). The proportion of patients with long time-to-progression (> 8 weeks) was also higher in the first-line than the salvage chemotherapy group (81.0 % [47 /58] vs. 61.8 % [34 /55], respectively; P = 0.036). Although, the response to chemotherapy was not associated with stent migration or re-stenosis, a long time-to-progression (adjusted hazard ratio [aHR] = 0.29, 95 % confidence interval [CI] 0.13 – 0.67) and first-line chemotherapy (aHR = 0.45, 95 %CI 0.22 – 0.93) were protective factors against re-stenosis in the multivariate analysis. In patients who received first-line chemotherapy, the median duration of patency of covered and uncovered stents was 20 weeks (95 %CI 11 – 29) and 33 weeks (95 %CI 18 – 48), respectively (P = 0.317). Conclusions: A long time-to-progression and first-line chemotherapy were significant protective factors against re-stenosis. In chemotherapy-naïve gastric cancer patients with pyloric obstruction, placement of an uncovered stent followed by chemotherapy can be considered to increase stent patency.